Comparative study on the possible ameliorative effects of imatinib and ibudilast in a rat model of multiple sclerosis - Monica Gamal Fawzy; Mohsen Sami Selim; Omayma Anwar Khorshid; Laila Ahmed Rashed; Miran Atif Elkordy; Noha Samir Abdel Latif (Future Journal of Pharmaceutical Sciences)
Abstract Background This is an experimental comparative study of the ameliorative effects of imatinib and ibudilast in multiple sclerosis induced in rats by cuprizone. Forty healthy adult male rats were used and divided into five groups: normal control, solvent control, multiple sclerosis model, imatinib- and ibudilast-treated groups. To detect behavioural changes, hang wire test was done for motor assessment, Morris water maze test was done to assess long-term memory, and Y-maze test was done to assess short-term memory. The tests were done on the last day of the experiment. At the end of the study, rats were sacrificed, and brains were extracted. From the brain samples, the right hemispheres were used for measurement of biochemical parameters from brain homogenates. While the left hemispheres were used for pathological and immunohistochemical examination. Results Treated groups showed improvement whereas ibudilast showed improvement in the behavioural tests, MAPK, IL-17, TNF-α and histopathological examination. While imatinib showed improvement in NFκB, MBP, SOD and nitric oxide. Conclusion Both imatinib and ibudilast had neuroprotective role in multiple sclerosis; however, ibudilast showed better results in improving neurological manifestations, biochemical and pathological parameters. This sets ibudilast as a promising drug to help slow down the pathogenesis of multiple sclerosis.